STRATEGI PENGEMBANGAN USAHA PENGELOLAAN HUTAN TANAMAN RAKYAT (HTR) DI DESA BUMI BERINGIN KECAMATAN LUWUK KABUPATEN BANGGAI - Raja, Eduardus (Katalogis, 2016)
Commmunity forest is a plantation forest in production forest that was developed by individuals or cooperatives to increase the potential and quality of production by implementing silviculture practices to ensure the sustainability of forest resources. The village of Bumi Beringin has gained a license for utilization of forest products in Community Forest by the Regent of Banggai (on behalf of the Minister of Forestry) covering 100 hectares, divided into 13 (thirteen) people who are members of forest farmers group Bersatu, but until now there is no implementation on the field due to the lack of strategies and right development patterns, so that there should be a research to obtain an appropriate development strategy in order for the the program development in Bumi Beringin Village can run good and right so as to improve the welfare of local communities. This research was conducted for 3 months starting in September 2015 until November 2015. The research was located in the Bumi Beringin Village, Luwuk Sub-district, Banggai District, Central Sulawesi. A strategy of community forest management development of forest farmers group Bersatu of Bumi Beringin village, Luwuk sub district, Banggai district is in quadrant II (2.45; 2.69) which means the diversification strategy of using strength to take advantage of opportunities or Strength-Treath Strategy (ST). The best pattern of community forest management development in Bumi Beringin Village, Luwuk Sub-district, Banggai District is a partnership pattern towards the Independence.